Empowerment of sanitation Dakwah of Pesantren in Pesantren Jagat Arsy, South Tangerang - Sumantri, Arif; Raharyanti, Fenny; Jalaludin, Juliana; Jauharoh, Siti Nur Aisyah (Institute of Research and Community Services Diponegoro University (LPPM UNDIP), 2024)
Background:The urgency of sanitation is enforced as a promotive and preventive form before exposure to various diseases in all places, including in educational institutions, including in pesantrenenvironments. The objectives of this study is providinginterventions on the knowledge, attitudes and behavior of pesantrenstudents in empowering pesantrensanitation preaching and proving the truth that pesantrenas a product of Islamic thought, implements life as a whole (kaffah).Method:This study is a mixed method, both quantitative and qualitative analysis at thePesantrenJagat Arsy World Civilization, South Tangerang City, over a period of two months. This research uses an experimental design. Sampling was carried out purposively consisting of 30 students. Criteria are determined by assessing the level of knowledge, attitudes and behavior by conducting a pre-post test assessment, in questions made on a Likert Scale. Univariate data presentation is shown in the distribution of respondent characteristics, while the significance of changes after intervention uses the paired T statistical test with α= 0.05. Qualitative data collection from the Islamic boarding school took the form of in-depth interviews, related to the delivery of hygiene and sanitation material, policy support and participation in the Islamic boarding school environment in empowering Islamic boarding school sanitation preaching.Results:An effective method for conveying clean and healthy living habits is by providing consequences and examples, so that after receiving the intervention there is a significant difference between the pre-post test on attitude and behavior variables with a p value of 0.027 and 0.011.Conclusion:The attitudesand behavior of students in empowering Islamic boarding school sanitation da'wah experience significant differences after receiving intervention and the truth that Islamic boarding schools, as a product of Islamic thought, implement life as a whole (kaffah) more effectively by getting policy support so that Islamic boarding school sanitation preaching can run well.